Study on strain response of X80 pipeline steel during weld dent deformation. (May 2021) - Zhu, Lixia; Luo, Jinheng; Wu, Gang; Han, Jun; Chen, Yongnan; Song, Chengli
Highlights: Strain evolution of X80 linepipe with dent in the weld zone is studied. Strain hardening model is established and dislocation configuration is discussed. The maximum allowable dent depth in the weld of in-service pipeline is proposed. Abstract: Mechanical damage is one of the main factors affecting the service safety and service life of pipeline steel. The weld will cause cracking failure due to different strain response with different microstructure during deformation. In order to study the response characteristics and mechanism of the weld during deformation, the strain evolution process of the X80 pipeline steel in the weld zone is studied by finite element analysis (FEA) and experimental prefabrication of pipeline dent. The strain hardening model of the weld zone is established, and the dislocation configuration in different regions is discussed. The results show that the maximum strain gradually transfers from the weld to the heat affected zone (HAZ) when the depth of the dent is greater than 3% outer diameter, and the crack is finally generated at this stress concentration zone. The experiment verifies this phenomenon and shows that the established model can effectively evaluate the strain distribution and variation process of the weld zone with dent. It is believed that the microstructure of the weld is mainly fine ferrite with good strength and toughness; the microstructure of the HAZ is mainly bainitic ferrite with M/A islands distributed, which will hinder the movement of dislocations in ferrite under the external load, resulting in dislocation accumulation and stress concentration. As the depth of the dent increases, the density of dislocation at the grain boundary of the weld and the HAZ increases, and the dislocation slips continuously. The typical dislocation cell substructure appears in the HAZ, which reduces the uniform plastic deformation capacity and deformation capacity. Based on the simulation and experiment, it is proposed that the in-service pipeline should be repaired or replaced when the weld dent depth is larger than 3% outer diameter.